Congenital melanocytic nevus of the oral mucosa. - Yun, D.; Stein, S.L. (European Journal of Pediatric Dermatology, 2010)
Congenital melanocytic nevus of the oral mucosa is a rarely described lesion in the literature. We describe the case of an African American infant presenting with a pigmented lesion on the mandibular gingiva noted at 2-3 months of age. This report also highlights the difficulty in applying histopathologic criteria of congenital melanocytic nevi to oral mucosal lesions.